ONLINE TEACHING TOOLS FOR EDUCATORS - Tolibjonova Zuhro Bahtiyorovna; Nasimova Sohiba Yaxyayevna (PEDAGOGS, 2025)
Annotation: There is no one-size-fits-all method for teaching online. The benefits and drawbacks of various online platforms may vary depending on the course material, learning goals, and the preferences of both the instructor and the students. This post will show you how to teach on four popular online platform types: blended, hybrid, synchronous, and asynchronous.